A hybrid algorithm based on a new neighborhood structure evaluation method for job shop scheduling problem. (October 2015) - Gao, Liang; Li, Xinyu; Wen, Xiaoyu; Lu, Chao; Wen, Feng
Highlights: We proposed a hybrid PSO and VNS algorithm for job shop scheduling problem. We proposed a new neighborhood structure evaluation method to guide the algorithm design. The proposed algorithm solves the job shop scheduling problem effectively. Proposed algorithm has found many optimal solutions for some famous benchmark problems. Abstract: Job shop scheduling problem (JSP) which is widespread in the real-world production system is one of the most general and important problems in various scheduling problems. Nowadays, the effective method for JSP is a hot topic in research area of manufacturing system. JSP is a typical NP-hard combinatorial optimization problem and has a broad engineering application background. Due to the large and complicated solution space and process constraints, JSP is very difficult to find an optimal solution within a reasonable time even for small instances. In this paper, a hybrid particle swarm optimization algorithm (PSO) based on variable neighborhood search (VNS) has been proposed to solve this problem. In order to overcome the blind selection of neighborhood structures during the hybrid algorithm design, a new neighborhood structure evaluation method based on logistic model has been developed to guide the neighborhood structures selection. This method is utilized to evaluate the performance of different neighborhood structures. Then the neighborhood structures which have good performance are selected as the main neighborhood structures in VNS. Finally, a set of benchmark instances have been conducted to evaluate the performance of proposed hybrid algorithm and the comparisons among some other state-of-art reported algorithms are also presented. The experimental results show that the proposed hybrid algorithm has achieved good improvement on the optimization of JSP, which also verifies the effectiveness and efficiency of the proposed neighborhood structure evaluation method.